ETIKA DAN PERTANGGUNGJAWABAN PENGGUNAAN ARTIFICIAL INTELENGENCE DI INDONESIA - Nasman Nasman; Pudji Astuti; Dita Perwitasari (Jurnal Hukum Lex Generalis, 2024)
This research explores the criteria and standards essential to ensure that the use of Artificial Intelligence in Indonesia occurs ethically and responsibly. Identifying transparency, accountability, fairness, and data security and privacy as key pillars, the research underscores the importance of integrating ethical principles in all Artificial Intelligence development and deployment phases. Using a normative type of research by analyzing the existing legal and ethical framework and through legislative and comparative approaches, this research provides recommendations for strengthening AI regulations in Indonesia, thereby minimizing the risk of loss and increasing public trust in this technology.